The protein domains of the Dictyostelium microprocessor that are required for correct subcellular localization and for microRNA maturation. Issue 10 (2nd October 2016) - Kruse, Janis; Meier, Doreen; Zenk, Fides; Rehders, Maren; Nellen, Wolfgang; Hammann, Christian
ABSTRACT: The maturation pathways of microRNAs (miRNAs) have been delineated for plants and several animals, belonging to the evolutionary supergroups of Archaeplastida and Opisthokonta, respectively. Recently, we reported the discovery of the microprocessor complex in Dictyostelium discoideum of the Amoebozoa supergroup. The complex is composed of the Dicer DrnB and the dsRBD (double-stranded RNA binding domain) containing protein RbdB. Both proteins localize at nucleoli, where they physically interact, and both are required for miRNA maturation. Here we show that the miRNA phenotype of a Δ drnB gene deletion strain can be rescued by ectopic expression of a series of DrnB GFP fusion proteins, which consistently showed punctate perinucleolar localization in fluorescence microscopy. These punctate foci appear surprisingly stable, as they persist both disintegration of nucleoli and degradation of cellular nucleic acids. We observed that DrnB expression levels influence the number of microprocessor foci and alter RbdB accumulation. An investigation of DrnB variants revealed that its newly identified nuclear localization signal is necessary, but not sufficient for the perinucleolar localization. Biogenesis of miRNAs, which are RNA Pol II transcripts, is correlated with that localization. Besides its bidentate RNase III domains, DrnB contains only a dsRBD, which surprisingly is dispensable for miRNA maturation. This dsRBD can, however, functionally replace the homologous domain in RbdB. Based on the unique setup of the Dictyostelium microprocessor with a subcellular localization similar to plants, but a protein domain composition similar to animals, we propose a model for the evolutionary origin of RNase III proteins acting in miRNA maturation.